Surgical simulation in robotic-assisted thoracic surgery: training - Wahl, Tyler S.; Wei, Benjamin (Video-Assisted Thoracic Surgery; Vol 3 (November 2018): Video-Assisted Thoracic Surgery, 2018)
Surgical training in thoracic surgery now challenges trainees to master open and minimally invasive approaches. Strategies to improve training, specifically among robotic-assisted thoracic surgery, remain an area of interest needing continued advancement and standardization. Simulation has been proposed as a catalyst for such skill proficiency and training. With recent time constraints on surgical education, the role of simulation has become paramount to provide the additional exposure and opportunities to hone skill and performance levels to achieve the necessary proficiencies and learning curve. A vast array of robotic simulation curriculums and modules are cited in the literature, however, calls for universal standardized curriculums are resounding. A standardized curriculum will measure proficiency on any robotic simulator, standardize fundamentals in training, and provide more clear criteria for certification and credentialing. The curriculum should be robust and multifaceted, including didactics, observation, simulation, and hands-on performance.